Conversation and responsibility - McKenna, Michael, 1963- (Oxford : Oxford University Press, 2012)
In this book, Michael McKenna advances a new theory of moral responsibility, one that builds upon the work of P.F. Strawson.
Description based on online resource; title from PDF title page (viewed on Apr. 18, 2012).
Includes bibliographical references and index.
Keywords: Responsibility